2013
DOI: 10.1111/pan.12238
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐guided approach to the paravertebral space for catheter insertion in infants and children

Abstract: This technical description demonstrates the feasibility of placing PVNB catheters using a transverse in-line ultrasound-guided technique in a wide range of pediatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 22 publications
(29 reference statements)
1
35
0
1
Order By: Relevance
“…Single injection nerve blocks have a limited duration and the patients can benefit from the infusion of local anesthetic via catheters. The use of peripheral nerve block catheters is becoming more prevalent in the inpatient and outpatient settings [7,8,[15][16][17].…”
Section: Equipment Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Single injection nerve blocks have a limited duration and the patients can benefit from the infusion of local anesthetic via catheters. The use of peripheral nerve block catheters is becoming more prevalent in the inpatient and outpatient settings [7,8,[15][16][17].…”
Section: Equipment Overviewmentioning
confidence: 99%
“…Recently, there is a trend towards an increased use of peripheral nerve blocks (PNBs). They produce effective pain relief and have a low risk of morbidity [1,[6][7][8][9][10][11]. However, PNBs as a sole agent for pediatric anesthesia are still underutilized.…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative pain was controlled by a right PVBC and multimodal analgesia. Following surgery, while the patient remained under general anesthesia and in the lateral position, the T7 paravertebral space was identified using a high frequency ultrasound probe (Sonosite, 6-15MHz, 5 cm linear probe) connected to a Sonosite S-Nerve machine (Bothnell, WA) as described by Boretsky et al [1]. Under direct ultrasound visualization, a 9 cm, 18 gauge Tuohy needle (Pajunk Tuohy Sono, Geisingen, Germany) was inserted in-plane, from lateral to medial, in a slightly oblique orientation.…”
Section: Case Reportmentioning
confidence: 99%
“…Placement of a thoracic paravertebral nerve block catheter (PVBC) is a safe and effective method for providing postoperative analgesia for pediatric patients undergoing thoracotomy [1]. Few cadaveric studies showed that paravertebral catheters can be misplaced despite the correct placement of needle, but there is no case report of a catheter misplaced into the contra lateral paravertebral space [2].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Recently, ultrasound-guided PVBs and catheter replacement techniques have also been used effectively for pain relief after thoracic, cardiac and abdominal surgeries as an alternative to epidural analgesia in pediatric patients. [6][7][8][9] We report a 10-year-old male patient (30 kg, 140 cm, ASA I) who underwent left latissimus dorsi muscle transfer (free flap) surgery under general anesthesia (GA) because of biceps brachii muscle motor weakness and atrophy occurring after oral (OPV) and inactive polio (IPV) vaccination (Figure 1). A decision was made to perform thoracic PVBs (TPVBs) bilaterally after surgery for postoperative pain management.…”
mentioning
confidence: 99%